Gods without men - Kunzru, Hari (Hamish Hamilton, 2011)
"2008. The California desert. A four-year-old austistic boy, Raj Matharu, disappears in the winderness plunging his wealthy New York parents in to the surreal public hell of a media witch-hunt. But the desert is inexplicable and miraculous, and the Matharus' fate is bound up with that of others: a debauched British rock star, on the run from a failed relationship and the sordid excesses of his life; a former member of an extraterrestrial-worshipping cult, now middle-aged but still haunted by transcendent callings; and a teenage Iraqi refugee, who befriends a young black Marine while playing the role of 'Iraqi villager' in a military simulation exercise. Their lives converge in an odd, remote town, near a rock formation called the Pinnacles -- and among the tanged echoes and stories of all those who have travelled before them through this brutally powerful landscape."--Back cover.